1994
DOI: 10.1002/mrm.1910320306
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo13C and 31P NMR analyses of phosphocholine metabolism in rat glioma cells

Abstract: In vivo magnetic resonance spectroscopy (MRS) has revealed that phosphomonoesters (PME) such as phosphocholine (PCho) and phosphoethanolamine (PEth) are elevated in tumors and rapidly proliferating tissues. The regulation of PME levels and their relationship to proliferation are not well known. In the present study, we investigated the regulation of PCho and PEth levels in rat glioma cells grown in vivo and in vitro using 31P and 13C MRS. However, the ability of cells to produce choline endogenously is variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 33 publications
4
67
0
Order By: Relevance
“…In general, the consensus is that tissues with high proliferative potential or tissues that are oncogenically transformed are also highly cellular in the absence of compensating apoptotic mechanisms or limitations of vascular supply. Consistent with this, many studies strongly have suggested that the Cho peak detected by in vivo MRS may be elevated because the volume of interest is highly cellular (Chang et al, 1995;Miller et al, 1996b;Cheng et al, 2000b) or includes cells with high PCho which may be due to increased proliferative potential (Daly et al, 1987;Daly and Cohen, 1989;Gillies et al, 1994a;Mahmood et al, 1994;Aiken and Gillies, 1996;Aiken et al, 1996) or includes cells which are oncogenically transformed (Bhakoo et al, 1996;Aboagye and Bhujwalla, 1999;Ackerstaff et al, 2001). It was recently reported that in ex vivo high resolution MR spectra (which show much higher than the spectra obtained in vivo) of a biopsy from a cerebellar primitive neuroectodermal tumor, myo-inositol, taurine and phosphorylethanolamine contribute to the in vivo signal at 3.2 ppm, usually attributed to Cho-containing compounds (Tugnoli et al, 2001).…”
Section: Biological Aspects Of Selected Metabolites Detected By Protomentioning
confidence: 78%
See 2 more Smart Citations
“…In general, the consensus is that tissues with high proliferative potential or tissues that are oncogenically transformed are also highly cellular in the absence of compensating apoptotic mechanisms or limitations of vascular supply. Consistent with this, many studies strongly have suggested that the Cho peak detected by in vivo MRS may be elevated because the volume of interest is highly cellular (Chang et al, 1995;Miller et al, 1996b;Cheng et al, 2000b) or includes cells with high PCho which may be due to increased proliferative potential (Daly et al, 1987;Daly and Cohen, 1989;Gillies et al, 1994a;Mahmood et al, 1994;Aiken and Gillies, 1996;Aiken et al, 1996) or includes cells which are oncogenically transformed (Bhakoo et al, 1996;Aboagye and Bhujwalla, 1999;Ackerstaff et al, 2001). It was recently reported that in ex vivo high resolution MR spectra (which show much higher than the spectra obtained in vivo) of a biopsy from a cerebellar primitive neuroectodermal tumor, myo-inositol, taurine and phosphorylethanolamine contribute to the in vivo signal at 3.2 ppm, usually attributed to Cho-containing compounds (Tugnoli et al, 2001).…”
Section: Biological Aspects Of Selected Metabolites Detected By Protomentioning
confidence: 78%
“…The Cho peak consists of water-soluble Cho-containing compounds, such as phosphocholine (PCho) and glycerophosphocholine (GPC), and free choline (Barker et al, 1994), versus membrane-bound phospatidylcholine (Miller et al, 1996a). In vivo MRS reveals that phosphomonoesters (PME), such as phosphocholine (PCho) and phosphoethanolamine (PEth), are elevated in tumors and rapidly proliferating tissues (Daly et al, 1987;Daly and Cohen, 1989;Gillies et al, 1994a). Furthermore, elevations in PCho and PEth correlate with increased cell growth or increased cell degradation, and have been shown to occur in human tumors, as well as in animal tumor models and cell lines.…”
Section: Biological Aspects Of Selected Metabolites Detected By Protomentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, enhanced phospholipid biosynthesis and reduced phospholipid breakdown were observed in long-term chronic situations such as tumors and high phosphomonoester (PME) levels have been hypothesized to be the best biochemical marker to distinguish some cancerous from normal tissues (16,17,43,52,55,62,65) and to monitor tumor treatment outcome (69,75). Some but not all of these observations might be due to the fact that under certain conditions PC strongly correlates with cell proliferation (4,6,21,26,62,68,72,82). Ting et al (80) compared the metabolism of different human breast cancer cells and normal mammary epithelial cells with a similar proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Among other things, measurement of tumor energetics by 31 P-NMR spectroscopy provides useful information about tumor oxygenation/ hypoxia and potential therapeutic resistance. However, there is some controversy about the relevance of the additional parameters that can be monitored in tumors via phosphorous NMR, e.g., phospholipid metabolism (15,16,26,43,44,62,68,79). It was previously reported that most human tumors contain high concentrations of phosphomonoesters, with the major compounds being identified as phosphorylethanolamine (PE) and phosphorylcholine (PC) (15,54,72).…”
mentioning
confidence: 99%